Challenging pacemaker implantation in a patient with acquired dextrocardia after pneumonectomy, skoliosis and complete heart block - Hamm, Karsten; Haghi, Dariusch; Borggrefe, Martin; Kuschyk, Jürgen (Interactive cardiovascular and thoracic surgery, 2010)
Pacemaker implantation after pneumonectomy is rare and there have been no previously reported cases of acquired dextrocardia after implantation. The authors report the case of a pacemaker implantation in a patient with complete heart block, impaired left ventricular function, sclerosis of heart valves and radiation induced vasculopathy resulting in ostial stenosis of the right coronary artery 30 years after radiochemotherapy in childhood. Acquired dextrocardia after right pneumonectomy for mucoepidermoid carcinoma made implantation a challenge due to and poor fluoroscopic visualization of the heart and increased radio-opacity of the right chest when compared to congenital dextrocardia.
Gesehen am 03.03.2023